2017
DOI: 10.18632/oncotarget.22520
|View full text |Cite
|
Sign up to set email alerts
|

Role of preoperative magnetic resonance imaging and histological assessment in identifying patients with a low risk of endometrial cancer: a Korean Gynecologic Oncology Group ancillary study

Abstract: Preoperative identification of individuals at low risk of lymph node metastasis is key to the proper management of endometrial cancer. This study evaluated the role of preoperative assessment based on magnetic resonance imaging (MRI) and histological analysis in identifying a group having a low risk of lymph node metastasis. Data of 529 patients with endometrial cancer were obtained from a prospective multicenter database, between January 2012 and December 2014. Clinical staging, based on MRI and histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Faced with our results and literature findings demonstrating the under staging of endometrial cancer on preoperative endometrial samples, other parameters can be considered for surgical planning. Magnetic resonance imaging to evaluate myometrial invasion, 34 tumor volume, 35 and intraoperative staging estimation by the analysis of cryopreserved specimens 36 can also contribute to surgical planning.…”
Section: Discussionmentioning
confidence: 99%
“…Faced with our results and literature findings demonstrating the under staging of endometrial cancer on preoperative endometrial samples, other parameters can be considered for surgical planning. Magnetic resonance imaging to evaluate myometrial invasion, 34 tumor volume, 35 and intraoperative staging estimation by the analysis of cryopreserved specimens 36 can also contribute to surgical planning.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fertility-sparing treatment (FST) might be considered a valid option for reproductive-aged patients with grade 1 or 2 endometrioid adenocarcinoma and no MI or MI <1/2 because they are commonly considered a ‘‘low-risk” population [ 2 5 ]. In low-risk populations, according to various criteria, the risk of lymph node metastasis ranged between 1.7% and 2.9% [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether EC patients are candidates for FST is usually determined by MRI and dilatation and curettage [ 1 ]. In previous studies, however, the matching rates between the preoperative assessment and postoperative pathology were not high enough, causing concern about extending the candidates for FST [ 7 12 ]. MRI is considered a suitable tool for the preoperative staging of ECs.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (5) reported that ADC has the potential to discriminate intermediate-and high-risk stage I EC patients, whereas Lee et al (6) reported that preoperative MRI and histological results can be used for identification of low-risk EC patients. However, results of risk prediction of EC using MRI or IHC alone show significant variations (6)(7)(8)(9). Therefore, it is important to explore the effect of combining preoperative MRI features and IHC markers on the predictive value for high-risk EC.…”
Section: Introductionmentioning
confidence: 99%